The Tahtsa Ranges Atmospheric River Experiment (TRARE): experimental design and case studies - Kelly M. Hurley; Jeremy E. Morris; Émile Cardinal; Derek E. Gilbert; Anna R. Kaveney; Bruno S. Sobral; Hadleigh D. Thompson; Julie M. Thériault; Stephen J. Déry (Discover Atmosphere)
Abstract In September and October 2021, the Tahtsa Ranges Atmospheric River Experiment (TRARE) was held in western Canada to collect detailed hydrometeorological data on atmospheric rivers and other mid-latitude storms impacting British Columbia’s upper Nechako Watershed and surrounding regions. A total of 11 precipitation events including six atmospheric rivers yielded a cumulative precipitation total of 250 mm at Huckleberry Mine, our primary field site. This paper summarizes the TRARE experimental setup that included six principal field sites including Huckleberry Mine along with nine secondary ones where high-frequency (up to the minute-scale) hydrometeorological data were collected. This included an array of four micro rain radars, four optical disdrometers, four meteorological stations, a hotplate precipitation gauge, a weighing precipitation gauge, and a network of tipping bucket rain gauges plus water measurements including levels, discharge and temperatures for two alpine creeks and water levels for one lake. Additional measurements of vertical atmospheric profiles from radiosondes supplemented by in-situ visual observations at two sites provide a comprehensive database to characterize storm evolution and precipitation distribution in the area. The paper highlights sample data from two case studies including an intense atmospheric river that made landfall near the study area. The TRARE field campaign’s accomplishments, challenges and lessons learned are then discussed. Furthermore, we report on the learning outcomes, outreach activities and communication strategy from TRARE. The paper closes with the next steps for atmospheric river monitoring and research in north-central British Columbia.